2015
DOI: 10.2118/171664-pa
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Characterization of Hydraulically Fractured Shale-Gas Reservoirs—Production History Matching

Abstract: Advancements in horizontal-well drilling and multistage hydraulic fracturing have enabled economically viable gas production from tight formations. Reservoir-simulation models play an important role in the production forecasting and field-development planning. To enhance their predictive capabilities and to capture the uncertainties in model parameters, one should calibrate stochastic reservoir models to both geologic and flow observations.In this paper, a novel approach to characterization and history matchin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(2 citation statements)
references
References 35 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…Other approaches are: artificial neural networks (Al-Anazi and Babadagli, 2009), Markov Chain Monte Carlo (Ginting et al, 2011), probability perturbation method (Suzuki et al, 2007), recovery curve method (Ghaedi et al, 2015), Discrete Fracture Network flow simulator (Lange, 2009), Ensemble Kalman Filter (Lu and Zhang, 2015;Nejadi et al, 2015), and Kernel principal component analysis (Paico, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other approaches are: artificial neural networks (Al-Anazi and Babadagli, 2009), Markov Chain Monte Carlo (Ginting et al, 2011), probability perturbation method (Suzuki et al, 2007), recovery curve method (Ghaedi et al, 2015), Discrete Fracture Network flow simulator (Lange, 2009), Ensemble Kalman Filter (Lu and Zhang, 2015;Nejadi et al, 2015), and Kernel principal component analysis (Paico, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The AHM method in the petroleum engineering field was first proposed for conventional sandstone reservoirs to deduce the formation properties that are difficult to measure directly from field-scale historical production data [17]. During the past two decades, AHM has been extended to solve various inverse problems such as (i) interpretation of relative permeability from laboratory core flooding data, (ii) estimation of permeability and skin factor of multilayered reservoir from injection-falloff test and (iii) characterization of hydraulic fractures in shale reservoirs from seismic and/or production data [18][19][20]. These previous studies indicated that the AHM is capable of deriving reasonable results with the proper experimental design and the implementation of robust algorithms.…”
Section: Introductionmentioning
confidence: 99%